2006
DOI: 10.2460/ajvr.67.8.1307
|View full text |Cite
|
Sign up to set email alerts
|

Genomic expression patterns of mitral valve tissues from dogs with degenerative mitral valve disease

Abstract: Evaluation of global expression patterns provides a molecular portrait of mitral valve disease, yields insight into the pathophysiologic aspects of DMVD, and identifies intriguing genes and pathways for further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
108
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(122 citation statements)
references
References 44 publications
12
108
2
Order By: Relevance
“…It has been suggested that MMVD is functionally and pathologically similar in humans and dogs [13]. In a previous study, increased circulating 5-HT concentration as a potential source of heightened 5-HT signaling was demonstrated in small dogs with MMVD [11]. 5-HT concentration was decreasing with the increase of MMVD severity [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that MMVD is functionally and pathologically similar in humans and dogs [13]. In a previous study, increased circulating 5-HT concentration as a potential source of heightened 5-HT signaling was demonstrated in small dogs with MMVD [11]. 5-HT concentration was decreasing with the increase of MMVD severity [13].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to appetite, 5-HT interacts with leptin, the first identified adipokine. In the cardiovascular system, it has been recently reported that 5-HT has a role in the development of mitral valve disease [11]. 5-HT-related mechanism which is increased 5-HT signaling or decreased 5-HT clearance may lead to valvulopathy in humans and animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies do not reveal which are the genes responsible for the particular disease, but do allow the assessment of gene expression, as they enable the analysis of the whole genome. Gene expression may play a role in the development and progression of heart diseases and the studies can be used to further our knowledge of canine MVD by showing differences between healthy and diseased dogs, as well as between the different stages of MVD (6,18). They might provide not only information about the disease process, but also possible new biomarkers to be used in cardiovascular diagnostics and therapy assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on affected tissues have shown up-regulation of MMP-1 and MMP-9 as well as collagen III (25), serotonin receptor 2B (18), MMP-1, MMP-14, and tissue inhibitors of metalloproteinases (TIMPs) such as TIMP-2, TIMP-3, and TIMP-4 (2, 3). Studies of tissue from affected hearts have also shown down-regulation of gene expression in the course of mitral valve disease, namely down-regulation of the microfibrillar, glycoprotein, and noncollagen extracellular matrix genes, TGF-ßR2, TGF-ß R3, and connective tissue growth factor (25); several MMPs, including MMP-2 (2), MMP-1, and MMP-13 (4); and TGF-ß3, TßR-II, αSMA, and MMP-3 (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation